2019
DOI: 10.37080/nmj.66
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and Its Associated Factor among Young Adults in Selected College of Kathmandu Valley Province-3

Abstract: Introduction: Insomnia has found to have many effects and risks on young adult and also has reduced economic productivity of the individuals as well as country. The prevalence of insomnia in Nepalese college students might be high as there is ineffectiveness of education system in addition to the further practical courses. Thus, the main aim of this study was to find out the prevalence of insomnia and its associated factors among young adult in selected college of Kathmandu. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Research in Pakistan shows 40.74% of medical students experience insomnia [33]. Then in Nepal, about 90% of college students experience insomnia [54]. In contrast to other studies, research in Lebanon showed a lower rate of 10.6% of students experiencing insomnia [55].…”
Section: B -Clinical Sciences Psychiatrymentioning
confidence: 74%
“…Research in Pakistan shows 40.74% of medical students experience insomnia [33]. Then in Nepal, about 90% of college students experience insomnia [54]. In contrast to other studies, research in Lebanon showed a lower rate of 10.6% of students experiencing insomnia [55].…”
Section: B -Clinical Sciences Psychiatrymentioning
confidence: 74%